Cerrados in Argentina?: Structure, diversity and biogeography of the woody component of a savanna in the Misiones Province - Velazco, Santiago José Elías (2018)
The Teyú Cuaré field, in Misiones province, Argentina, has been renowned for its flora and physiognomy, which led researchers to indicate that it could be a relict of Cerrado biome. We analyzed the floristic structure of the woody component of a savanna community in this site, and discussed the processes that could contribute to the permanence of this vegetation type over time. Perimeter and height of all woody individuals ≥ 10 cm of perimeter at soil height were collected in 12 square plots (400 m2 each one). We found 15 families and 17 species in our site and compared the woody flora surveyed at this site with the flora of other Cerrado areas from Brazil and Paraguay. Leptolobium elegans had the highest importance value. The woody flora of the area is closely related to the Cerrado areas from Paraná state in Brazil and Canindeyú and Amambay in Paraguay. This site probably reflects old open physiognomies which were predominant in Misiones and Southern of Brazil in the late Pleistocene and middle Holocene. We inferred that the permanence of open physiognomies at Teyú Cuaré is probably related to mechanisms that act at different levels, such as geological, edaphic, anthropic, and fire disturbance.